Correlations between hydrochar properties and chemical constitution of orange peel waste during hydrothermal carbonization. (October 2018) - Xiao, Kangxin; Liu, Huan; Li, Yang; Yi, Linlin; Zhang, Xiuju; Hu, Hongyun; Yao, Hong
Graphical abstract: Highlights: The effects of feedstock constitution on hydrochar properties were investigated. Cellulose and hemicellulose were favor of developing microsphere structure. Cellulose and hemicellulose were able to enhance diverse oxygenous groups. Lignin improved the yield of hydrochar and its benzene ring structure. Changes in feedstock components imply interactions in hydrothermal process. Abstract: For efficient hydrothermal treatment of biomass, this study aims to figure out the correlations between complex chemical constitution of orange peel (OraPeel) as typical bio-waste and the physicochemical structure of its derived hydrochar, which could be utilized to adjust hydrochar properties for specific applications (e.g., adsorbent, fuel) by regulating respective proportions of each component in bio-waste. Cellulose, hemicellulose and lignin were used as the control variables of feedstocks composition in this work. After hydrothermal process, lignin added feedstock produced more hydrochar, which contained rougher surface with nearly doubled BET areas and more benzene rings. Hemicellulose-aided hydrochar possessed higher density of carbonaceous microspheres and richer hydroxyl. This char was simultaneously covered by more esters or lactones with more aromatic oxygen-containing groups inside. Similar to hemicellulose, cellulose improved the formation of diverse oxygenous groups but reduced the size of microspheres on hydrochar.